Nove meses de consumo: da maternidade à vulnerabilidade - Barreto, Alice Medeiros (2012)
This study is a research proposal from the scene of pregnant women, bringing out the major physical changes, social, but mainly focusing on the role of the consumer behavior of this vulnerable group. Thus, we seek to examine the woman and mother, but with her wrapped in a family situation, social culture, economic and peculiar, which influences their customs and decisions throughout pregnancy and in other social interactions experienced at this stage. All these actors participate actively in the construction and transition to new maternal identity. Motherhood requires only the woman's decision to "be a mother", or a combination of two identities "being a mother" and "being professional". Many other changes occur in this reversal of identities present in the three standards of identity proposed by Fursman (2002). This study sought answers to identify the context in which to appeal to the consumer the woman during pregnancy may be taken to behave vulnerable. From a qualitative approach, the research used in-depth interviews and videography to collect information about the speech and behavior of consumption of 15 pregnant women. For the analysis, the researcher was based on dimensions related to consumer vulnerability model proposed by Baker et. al. (2005): Individual Characteristics, Individual States, external conditions and experiences of vulnerability in the context of consumption, serving as a maternal context. Research suggests that there is a strong influence of external factors that challenge the pregnant woman consumption, in addition, identifies consumerism justified and extended by others during pregnancy. He saw the justification of consumption by assigning it the vision of "being a mother" and preconceived myth of motherhood.